Board characteristics, firms’ specific factors and financial performance: evidences from ACE Market in Bursa Malaysia / Mohamad Azwan Md Isa, Nor Hazila Ismail and Maizura Mohd Isa. - Md Isa, Mohamad Azwan; Ismail, Nor Hazila; Mohd Isa, Maizura (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2019)
Financial performance is of great importance that must be looked into particularly by a firm’s management, shareholders and lenders when analysing success or failure of the firm. It is also one of the crucial criteria, which must be examined by potential investors, government regulatory bodies and other stakeholders before deciding to make any decisions about the firm. Hence, this study aims to investigate the relationships and impacts of five (5) firms’ specific factors, namely diversified board members’ gender, board’s independence, the firm’s growth, leverage and market capitalization on firms’ financial performance, which is measured by return on asset (ROA) and Tobin-Q. This study applies the methods of descriptive statistics, Pearson correlation and multiple regressions to test and analyse the selected variables. Using 210 firm-year panel data or observations for periods from year 2012 to 2017 of 35 firms listed in ACE Market of Bursa Malaysia, we have found that leverage and market capitalization are the two key factors that pose negative and positive significant influences on firms’ financial performance, respectively. These findings suggest that firms must strictly observe the optimal debt or leverage level as this will affect firms’ financial performance that eventually has impacts on firms’ value and shareholders’ wealth.